Development of total bed material load equation for high gradient rivers in Malaysia / Assoc. Prof. Dr. Shanker Kumar Sinnkaudan, Mohd Sofiyan Sulaiman and Dato' Prof. Ir. Dr. Sahol Hamid Abu Bakar - Sinnkaudan, Prof. Dr. Shanker Kumar; Sulaiman, Mohd Sofiyan; Abu Bakar, Dato' Prof. Ir. Dr. Sahol Hamid (Research Management Institute (RMI), 2011)
The sediment transport study deals with the analysis of sediment particles and flow characteristics. The ignorance of sediment transport component during hydraulic design will bring a severe damage to the hydraulic structure and river itself. The understanding of sediment transport has led to extensive research done by past researchers. In Malaysia, the studies were conducted by Ab. Ghani (1993), Abu Hasan (1998), Yahaya (1999), Ariffin et al. (2001), Ibrahim (2002), Sinnakaudan (2003) and Sinnakaudan et al. (2006). On the other hand, a broad sediment study was also conducted abroad by White et al. (1975), Brownlie (1981), Yang & Molinas (1982), Shen & Hung (1983), Raphelt (1990), Nakato (1990), Karim (1998), Woo et al. (1993), Molinas & Wu (2001), Nagy et al. (2002), Wilcock & Crowe (2003), Wu et al. (2004) and Duan et al. (2006). Few studies have specifically catered to the sediment transportation in highland rivers as cited in Ashida and Michiue (1972), Smart (1984) and Mizuyama (1977). However, there is no evidence on sediment transport studies conducted specifically for highland rivers in Malaysia though a variety of sedimentation and erosion problem currently emerge in the Malaysian highlands. Many pristine highland watersheds which were developed later induced problems to the river morphology and its stability.